2012
DOI: 10.2500/aap.2012.33.3529
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the association between atopic conditions and tympanostomy tube placement in children

Abstract: This study assesses the relationship between otitis media and atopic conditions in children by comparing the incidence of tympanostomy tube placement between children with and without atopic conditions: asthma, allergic rhinitis, and atopic dermatitis. Study subjects were a cohort of 323 healthy children who participated in a study of vaccine response. All episodes of tympanostomy tube placement and physician diagnoses of allergic rhinitis and atopic dermatitis were collected through comprehensive medical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
6
17
0
Order By: Relevance
“…Children with asthma or other atopic conditions had higher rates of tympanostomy tube placement (a surrogate marker for frequent and persistent ear infections) than those without asthma (risk ratio [RR], [95% CI]: 1.53 [0.93-2.53] or other atopic conditions (RR: 1.70 [1.01-2.86]). 30 Other studies corroborated these study findings with adjusted ORs of 1.40 to 2.70. 36-39 …”
Section: Effect Of Atopic Conditions On the Risk Of Microbial Infectionssupporting
confidence: 69%
See 2 more Smart Citations
“…Children with asthma or other atopic conditions had higher rates of tympanostomy tube placement (a surrogate marker for frequent and persistent ear infections) than those without asthma (risk ratio [RR], [95% CI]: 1.53 [0.93-2.53] or other atopic conditions (RR: 1.70 [1.01-2.86]). 30 Other studies corroborated these study findings with adjusted ORs of 1.40 to 2.70. 36-39 …”
Section: Effect Of Atopic Conditions On the Risk Of Microbial Infectionssupporting
confidence: 69%
“…Also, oral corticosteroid therapy among patients using vitamin D was not associated with increased risk of pneumonia but decreased the risk of pneumonia. 99 The study findings described above on the association of asthma with the increased risks of serious pneumococcal disease, 28 B pertussis , 50 S pyogenes upper respiratory infections, 40 recurrent/persistent otitis media, 30 H1N1 influenza, 56 community-acquired E coli BSI, 52 and herpes zoster 91 among patients with asthma were independent of the use of inhaled or systemic corticosteroids. Talbot et al 31 reported similar findings.…”
Section: Potential Factors Affecting the Association Between Atopic Cmentioning
confidence: 88%
See 1 more Smart Citation
“…(11) Since its development, it has been extensively used in asthma research and has shown excellent construct validity and reliability (0.72–92) of the criteria. (11, 2428) As most subjects with probable asthma (85%) became definite asthma over time we combined both probable and definite asthma. (11) The onset date of asthma (asthma index date) by PAC, was defined as the earliest constellation of symptoms found in the medical record that met the PAC for asthma regardless of physician diagnosis of asthma.…”
Section: Methodsmentioning
confidence: 99%
“…211 Indeed, previous studies showed that people with asthma had increased risk of microbial infections than those without asthma. 1220 A recent prospective study that compared rates of H1N1 infection between children with and without asthma showed that children with asthma had a higher risk of H1N1 infection during the second peak of the pandemic than non-asthmatics. 21 …”
Section: Introductionmentioning
confidence: 99%